Investigating the role between glycosaminoglycan immobilization approach and protein affinity - Cornell, Nicholas; Griffin, Donald (Frontiers in Biomaterials Science, 2023)
Glycosaminoglycans (GAGs) are linear polysaccharides commonly used to impart bioactivity into synthetic hydrogels through their broad electrostatic-based protein-binding capabilities. In vivo, GAGs are immobilized through a single linkage point and function as semi-rigid ligands that are capable of limited conformation to proteins to enable high affinity interactions, concentration gradients, and co-signaling. Most GAG immobilization strategies in biomaterials target modification of the GAG repeat unit and produce multiple linkage points which effectively turns the GAG into a multifunctional crosslinker. In this study, we utilize real-time monitoring of binding kinetics to investigate the effects of GAG immobilization approach on GAG-protein binding. We show that GAGs immobilized through a single linkage point (GAGSingle) possess enhanced protein binding compared with GAGs immobilized at several points (GAG¬Multi¬). This effect is demonstrated for multiple GAG and protein types, indicating a broad applicability and importance to GAG use in biomaterials.